KUALITAS SEMEN BEKU BABI DUROC DALAM PENGENCER TRIS MODIFIKASI DENGAN WAKTU EKUILIBRASI YANG BERBEDA (The frozen sperm quality of duroc pig in modified tris diluent with different equilibration time) - Selsiana Dongkot; Aloysius Marawali; Thomas M. Hine; Wilmientje M. Nalley (JURNAL NUKLEUS PETERNAKAN, 2022)
This study aimed to examine the quality of frozen sperm of duroc boar in modified Tris diluent with different equilibration time. Semen was collected from two duroc males and evaluated macroscopically and microscopically. Semen with motility 75%, concentration 200x106 cell/mL and abnormality <20% was diluted in Tris modified diluent, then held for two hours at room temperature (27-28ºC). The semen that has been in the holding time is then centrifuged at 2000 rpm for 15 minutes. The pellet from centrifuge were diluted again with modified Tris diluent + 3% glycerol. The diluted semen was packed in 0,50 mL mini straws and equilibrated according to the treatment equilibration time, namely P1: 1 hour equilibration time, P2: 2 hour equilibration time, P3: 3 hour equilibration time. After equilibration , it was frozen over liquid nitrogen vapor (-110ºC) at a distance of 5 cm for 10 minutes, then stored in liquid nitrogen (-196ºC) and left for 24 hours. Then thawing with warm water at 37ºC for 30 seconds in a water bath. The result showed that motility, viability, abnormality, intact plasma membrane and recovery rate were significantly higher (P<0,05) at two hour equilibration , namely 23.12%, 45.44%, 4.65%, 50,15%, 33.03% respectively compared to one and two hour equilibration time, namely 20%, 42.17%, 8.19%, 42.67%, 28.57% and 16,87%, 36.39%, 7.64%, 37.73%, 24.99% respectively. This study conclude that the equilibration time of two hours resulted in higher quality of frozen sperm of duroc boar than one and three hours.